Empowerment of MSMEs in Bhinneka Village, Setu Babakan, and Pulau Untung Jawa Tourist Villages Through Web Applications and Indonesian Tourism Village Award Assessment - Budilaksono, Sularso; Febrianty, Febrianty; Kencana, Woro Harkandi; Gantina, Devita (Society : Jurnal Pengabdian Masyarakat, 2024)
The advent of information technology has permeated all aspects of life, facilitating a myriad of conveniences in daily human activities, including those within the tourism industry. The nomination of Bhinneka Village, Setu Babakan Betawi Cultural Village, and Pulau Untung Jawa tourist village for the 2021 Indonesian Tourism Village Award underscores the integration of technological advancements in the tourism sector. Nevertheless, Micro, Small, and Medium Enterprises (MSMEs) operating within these tourist villages confront several challenges related to the production, marketing, and sales of their offerings. To mitigate these challenges, tailored assistance and training programs are being deployed with the objective of empowering MSMEs to enhance their business operations and to adeptly leverage digital platforms for promotion, marketing, and sales activities. This initiative necessitates a collaborative approach, wherein managers of tourist villages, Pokdarwis, and MSME stakeholders collectively endeavor to execute both traditional and digital marketing strategies, thereby ensuring optimal service delivery to tourists. The deployment of the Wisataqu.id application emerges as a pivotal tool in this context, offering substantial support to tourism village managers and surrounding MSMEs in their pursuit of digital promotion and marketing. This integration of digital tools is poised to not only elevate the visibility and accessibility of these cultural destinations but also to stimulate local economies by fortifying the tourism sector's foundation— the MSMEs.